Associations of TNFRSF1A Polymorphisms with Autoimmune Thyroid Diseases: A Case-Control Study - Shao, Xiao-Qing; Ding, Xiao-Lian; Mu, Kaida; Wang, Xuan; An, Xiao-Fei; Yao, Qiu-Ming; Li, Ling; Li, Qian; Song, Rong-Hua; He, Shuang-tao; Xu, Jian; Zhang, Jin-An (Hormone and Metabolic Research, 2018)
Previous studies have shown associations of polymorphisms in the tumor necrosis factor (TNF) receptor super family member 1A (TNFRSF1A) gene with several groups of inflammatory and autoimmune related diseases, but associations of TNFRSF1A polymorphisms with autoimmune thyroid diseases (AITD), mainly including two sub-types of Hashimoto’s thyroiditis (HT) and Graves’ disease (GD), in the Chinese Han population is unclear. A case-control study of 1812 subjects (965 AITD patients and 847 unrelated healthy controls) was conducted to assess AITD associations with five single nucleotide polymorphisms (SNPs), including rs4149576, rs4149577, rs4149570, rs1800693, and rs767455 in the TNFRSF1A gene locus. Genotyping was performed and evaluated using the platform of ligase detection reaction. No significant difference was observed in the allele and genotype frequencies between HT or GD patients and controls in any of the five SNPs in the TNFRSF1A gene (all p values >0.05). However, a moderate association of rs4149570 with HT was found after adjusting for age and gender [odds ratio (OR)=1.40, p=0.03]. No obvious difference was found in the haplotype distribution of any of the five SNPs in the TNFRSF1A gene between the AITD patients and controls. These data suggest that these five SNPs in the TNFRSF1A gene are not associated with AITD in the Chinese Han population, but rs4149570 shows a weak association with HT after adjusting for gender and age.
Keywords: TNFRSF1A; autoimmune thyroid diseases; single nucleotide polymorphism